Modelling IoT Untuk Monitoring Suhu dan pH Budidaya Ikan Nila Metode Dynamic System Development Method (DSDM) - Nizirwan Anwar; Achmad Fansuri; Agung Mulyo Widodo; Kundang Karsono Juman; Muhamad Bahrul Ulum (Prosiding SISFOTEK, 2021)
Fresh fish is one type of fish that is widely cultivated in Indonesia. Productivity and high production value are one of the good advantages of the aquaculture sector. But unfortunately, the cultivation is still very traditional. Water as one of the important factors in the cultivation, productivity, and quality of the fish produced, still has to be controlled manually which ultimately burdens the owner. Because of this, the use of the Internet of Things (IoT) is needed to support the productivity and effectiveness of cultivation. In system development, a microcontroller is used to monitor water quality which is closely related to temperature and pH in the pond. The data that has been collected by the microcontroller is then sent to the server computer via the internet and saved to a Firebase or Firebase database on the server computer, resulting in 15 tests obtained an average temperature of 29.82 oC (99.41%) and pH 6.66 (83 ,23%). Applications with the android platform that have been made connected to the network can automatically access data and information about water quality in ponds